Characteristics of sustainability partnerships - Study on Finnish multinational companies - Tomperi, Heidi (My University, 2017)
Sustainability and business partnerships are significant business trends, which appear together in a third trend: sustainability partnerships. These partnerships are formed to implement sustainability in business, but also to comply with increased stakeholder expectations towards sustainability. In this thesis, sustainability partnerships are examined from the company perspective, meaning the focus is on companies’ sustainability partnerships with various partners. The purpose is to examine their different characteristics, motives for companies to form these partnerships and their performance. To provide a theoretical background for this study, the literature review covers both business partnerships and sustainability in companies. These are then combined and supported with further theories of sustainability partnerships. Each theme is studied in terms of typical characteristics, motives theories and performance. Qualitative research design supports the intention to examine and understand sustainability partnerships. Furthermore, this study was conducted as an explorative interview study of nine sustainability managers in Finnish multinational companies. The data was analysed with content analysis. The findings of this study imply that sustainability partnerships are similar to business partnerships, with the distinction of sustainability focus and being more value-driven. The motives for forming these partnerships follow the motive theories in business partnerships and sustainability: resource-based view, transaction cost economics, stakeholder theory and institutional theory. Sustainability partnerships bring reputational and financial benefits to companies, and contribute to environmental and social improvements. The challenges in the partnership performance are related to choosing the right partner and measuring the partnership performance. Sustainability partnerships enable companies to learn about sustainability, and utilise their partners’ knowledge and expertise to improve their own sustainability performance and create value for themselves and their stakeholders.
Keywords: Sustainability partnerships; business partnerships; sustainability; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|